The Determinant Factors of Creative Economy Craftsmen Sustainability in South Sulawesi Province - Helda Ibrahim; Siti Amanah; Pang. S. Asngari; Ninuk Purnaningsih (Chemical Engineering Diponegoro University, 2013)
Creative economy craftsmen have big contribution to regional income and able to sustain in crisis. It can be seen on the average of Gross Domestic Product has employed 5.4 million in average for 2002-2009 with participation level of 5.8%. Therefore, a strategic sustainability is needed especially for the determinant factors of sustainability related to creative economy craftsmen. This research aims to observe the determinant factors of sustainability of creative economy craftsmen in Wajo and Bulukumba Regencies in South Sulawesi Province. Sample for the research was 215 creative economy craftsmen. Data collection is conducted on January to April 2012 consists of primary and secondary data. Research method was using prospective analysis to determine important factors to the sustainability of creative economy craftsmen that predict future alternatives. Result from Rap-UEK simulation for the composite of five dimensions showed a less sustainable status of 48.97%. Research results showed that there are six dominant or main factors in determining business sustainability of creative economy craftsmen, one place sale, coordination with the government and private sectors, capital source, increase in the product of creative economy business, business field and product development Doi: 10.12777/ijse.5.2.18-24 [How to cite this article: Ibrahim, H., Amanah, S., Asngari, P.S., and Purnaningsih, N. (2013). The Determinant Factors of Creative Economy Craftsmen Sustainability in South Sulawesi Province. International Journal of Science and Engineering, 5(2),18-24. Doi: 10.12777/ijse.5.2.18-24]